Green Space Impacts in Stream Corridor Settlement as an Effort to Form a “Greener” Neighborhood - Hanny Maria Caesarina; Noor Aina (Green Visioneers, 2018)
As the thousand city river, Banjarmasin has so many stream corridor settlement with specific character. Some new development brought new plans for those settlement which aim to make a greener neighborhood through some greening projects. This paper reviewed the green space impacts in stream corridor settlement as an effort to form a greener neighborhood. Field survey, observation and in depth interview also has been done with local residents to get clearer picture regarding how the greening project has given effect to their stream corridor neighborhood. The result shows that the green space impacts in stream corridor settlement in Banjarmasin still need to be improved in the future to achieve a greener neighborhood.